EKSISTENSI PEREMPUAN DALAM NOVEL CATATAN JUANG KARYA FIERSA BESARI: KAJIAN FEMINIS-EKSISTENSIALIS - Iswandi; Muhammad Adek (Universitas Terbuka, 2022)
Even though they are in the modern era, women in various parts of the world are still constrained by various shackles and it is difficult to show their existence. Literary works then become a platform for women to liberate themselves and emphasize their existence even though only symbolically. This study aims to describe the strategies, causes, and impacts of the existence of women in the novel Catatan Juang by Fiersa Besari based on the feminist existentialist study of Simone de Beauvoir. This research is a qualitative research with a library-based study. The analysis was carried out using the content analysis method. The results of this study can be conveyed as follows; (1) there are four strategies for the existence of women in the form of strategies, intellectual women, working women, social transformation women, and independent women, (2) the causes of the emergence of women's existence strategies, among others; social concerns, economic status, and thinking towards change.